2009
DOI: 10.1111/j.1365-2184.2009.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet radiation on human cutaneous nerve fibres

Abstract: Quantification of cell damage induced by UV radiation provides useful information for identification of new skin care compounds with neuroprotective properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…In accordance with previous studies, we confirm here that exposure to UV irradiation significantly decreases density of nerve fibres in human skin (2,8). These UV‐induced effects are desirable in attenuating pruritus observed in certain skin diseases (for example, psoriasis) where phototherapy is a therapeutic option.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with previous studies, we confirm here that exposure to UV irradiation significantly decreases density of nerve fibres in human skin (2,8). These UV‐induced effects are desirable in attenuating pruritus observed in certain skin diseases (for example, psoriasis) where phototherapy is a therapeutic option.…”
Section: Discussionsupporting
confidence: 93%
“…Samples were counterstained with DAPI and analysis was performed using a fluorescence microscope (Zeiss Axioskop 40; Carl Zeiss do Brasil Ltda., São Paulo, Brazil). Further details of this technique can be found elsewhere (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wallengren and Sundler showed that either UVB/A, PUVA or NB‐UVB decreased the number of intraepidermal (PGP 9.5 positive) nerve fibres (IENF) and dermal CGRP‐positive nerve fibres in non‐inflamed gluteal skin in ten patients with different skin diseases . Rodriguez et al also showed that IENF was lower in human skin samples after single ex vivo UVB or UVA irradiations.…”
Section: The Antipruritic Effect Of Phototherapymentioning
confidence: 98%